1998
DOI: 10.1007/978-94-011-4786-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and recombinant protein expression in Veggie-CHO: A serum-free CHO host cell line

Abstract: The dihydrofolate reductase-deficient Chinese hamster ovary cell line, DXB11-CHO, commonly used as a host cell for the production of recombinant proteins requires 7.5% serum-supplementation for optimal growth. Regulatory issues surrounding the use of serum in clinical production processes and the direct and indirect costs of using serum in large-scale production and recovery processes have triggered efforts to derive serum-independent host cell lines. We have successfully isolated a serum-free host that we nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 22 publications
(5 reference statements)
0
29
0
Order By: Relevance
“…Schlaeger (1996) and Heidemann et al (2000) have hypothesized that the hydrolysates provide cells with various low molecular weight nutrients that may be mimicked by an optimized initial free amino acid content of the protein-free medium. While Rasmussen et al (1998) and Burteau et al (2003) concluded that peptides in the hydrolysates could function as growth factors for CHO cells. Data from this work shows that F1 promoted Sf 9 cell growth most effectively in spite of its lowest concentration of free amino acids (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Schlaeger (1996) and Heidemann et al (2000) have hypothesized that the hydrolysates provide cells with various low molecular weight nutrients that may be mimicked by an optimized initial free amino acid content of the protein-free medium. While Rasmussen et al (1998) and Burteau et al (2003) concluded that peptides in the hydrolysates could function as growth factors for CHO cells. Data from this work shows that F1 promoted Sf 9 cell growth most effectively in spite of its lowest concentration of free amino acids (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have suggested that IGF-I could substitute for insulin in cell culture medium, either by exogenous addition (Rasmussen et al 1998), or by engineering the cell lines to produce their own IGF-I (Hunt et al 1997;Li et al 2000;Sunstrom et al 1998;Sunstrom et al 2000). However, exogenous addition of IGF-I is complicated by the presence of IGF binding proteins (IGFBP) secreted by the cells.…”
Section: Use Of Insulin and Insulin-like Growth Factors (Igf) In Cellmentioning
confidence: 99%
“…The clonal CHO cell line used as the host in our recombinant expression experiments was derived from previously described serum-free adapted CHO cells (Rasmussen et al, 1998). For 96-well plate screening, production temperatures and initial cell densities used had been tested and shown to be adequate for cell growth and response to control SMEs in preliminary experiments.…”
Section: Cell Cultivationmentioning
confidence: 99%